Single-cell RNA sequencing reveals intrahepatic signature related to pathobiology of duck hepatitis A virus type 3 (DHAV-3) infection - Yunsheng Zhang; Dingbang Ding; Shaofei Li; Qiong Pan; Jinlong Ru; Haonan Zhao; Guang Yao; Jie Wei; Shuaiqin Wang; Shuisheng Hou; Xia Wang (Poultry Science)
DHAV-3 is one of the main causative agents of duck viral hepatitis (DVH), an acute and highly lethal infectious disease in duck industry. However, the understanding of the pathogenesis of this virus in ducklings is limited. To dissect the molecular characteristics associated with pathobiology of ducklings to DHAV-3, we applied single-cell RNA-sequencing approach to profile the transcriptome of 1.4 million cells from 14 livers of DHAV-3 susceptible (S) and resistant (R) ducklings during viral infection and 4 uninfected healthy controls. We found that infected S ducks exhibited the activation of type I and II interferon pathways with elevated expression of interferon-stimulated genes (ISGs) compared to infected R ducks and healthy controls. DHAV-3 promoted proinflammatory phenotype and inhibited the cell apoptosis pathway of Kupffer cells of S ducks. Furthermore, we observed the elevated expression of host factor PLAC8 in S ducks and validated its ability to facilitate the infection of DHAV-3. We identified significant dysregulation of various genes in complement and coagulation cascades in hepatocytes2 exclusive to S ducks, together with over-secretion of ANGPTL4 from endothelial cells in S ducks which is confirmed to promote cellular migration, suggesting etiology of coagulopathic complications in ducks with severe DVH. Collectively, this study provides a rich resource for understanding the inflammatory immune signatures and cell communications underlying the pathogenesis of DHAV-3 infection, which may accelerate the development of better diagnostic methods and strategies for controlling this disease.